OsDSSR1, a novel small peptide, enhances drought tolerance in transgenic rice. (May 2018) - Cui, Yanchun; Li, Mingjuan; Yin, Xuming; Song, Shufeng; Xu, Guoyun; Wang, Manling; Li, Chunyong; Peng, Can; Xia, Xinjie
Highlights: OsDSSR1, a novel rice gene, encodes a small peptide. Transgenic plants over-expressing OsDSSR1 exhibit enhanced drought stress and decreased ABA sensitivity. OsDSSR1 over-expression promotes accumulation of compatible osmolytes, such as free proline and soluble sugars. OsDSSR1 over-expression plants displayed enhanced OsSodCc2 and OscAPX expression and superoxide dismutase and ascorbate peroxidase activities. OsDSSR1 over-expression plants enhanced drought tolerance by positively regulating some stress-related genes. Abstract: Small signaling peptides play important roles in plant development and responses to abiotic and biotic stresses. We have identified a novel small peptide gene in rice, OsDSSR1, which is expressed mainly in the root, stem, node, leaf, and panicle. OsDSSR1 expression is also induced by drought, salinity, ABA, and H2 O2 treatment. OsDSSR1 is localized in the nucleus and cytoplasm. Transgenic plants overexpressing OsDSSR1 exhibited enhanced drought stress tolerance and decreased ABA sensitivity as compared to the wild type. Overexpression of OsDSSR1 promoted the accumulation of compatible osmolytes, such as free proline and soluble sugars. OsDSSR1 -overexpressing plants displayed enhanced OsSodCc2 and OscAPX expression and superoxide dismutase and ascorbate peroxidase activities under drought stress. RNA-sequencing data revealed that the expression of 72 abiotic stress-responsive genes was significantly altered in homozygous transgenic plants. These stress-responsive candidate genes will aid in expanding our understanding of the mechanisms by which small peptides mediate tolerance in crop species.